ChemInform Abstract: AZT‐Prolinamide: The Nucleoside Derived Pyrrolidine Catalysts for Asymmetric Aldol Reactions Using Water as Solvent. Issue 13 (March 2015) - Naresh, Tumma; Kumar, Togapur Pavan; Haribabu, Kothapalli; Chandrasekhar, Srivari
Abstract New nucleoside‐based chiral prolinamides are synthesized and applied in enantioselective aldol reaction of aldehydes with ketones to give β‐hydroxyl carbonyl compounds in high yields with good stereoselectivity.